Forecast of Hourly Tropospheric Ozone Concentration in Quang Ninh using MLP and SVM - Thu Phuong, Nguyen Thi; Hung, Mac Duy; Nam, Duong Thanh; Dung, Nghiem Trung (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 3DO - 10.25073/2588-1094/vnuees.4604, 2020)
Support vector machine (SVM) and multilayer perceptron (MLP) were used to forecast hourly tropospheric ozone concentration at three locations of Quang Ninh, namely Cao Xanh, Uong Bi and Phuong Nam. Data used to train the models are the hourly concentrations of gaseous pollutants (O 3 , NO, NO 2 , CO) and meteorological parameters including wind direction, wind speed, temperature, atmospheric pressure, relative humidity measured in the 2016. Both models accurately forecast tropospheric ozone levels compared to the observation data. The correlation coefficients (r) of the models applied for the three locations range from 0.85 to 0.91. In addition, SVM exhibits a more accurate prediction than MLP, especially for those with large variations, i.e. high standard deviations.